No data, no market… really? REACH as co-management of chemical risks. Issue 114 (December 2020) - Maxim, Laura; Berger, Tristan
Highlights: Implementation of REACH does not respect the "no data, no market" principle. Precautionary principle was replaced by co-management of risks with the industry. Co-management supposes systematic compromise and a pedagogic approach. Co-management pragmatically responds to information and resources asymmetry. It is unclear to what extent REACH protects Europeans' health. Abstract: This article analyzes the European regulation REACH as a co-management policy tool for chemical risks. Whilst the existing literature on the topic either highlights the strong capacity of authorities to force the industry to produce the data needed for decision making, or criticizes the former's subordination to economic interests, this article takes a new approach showing how regulators and the industry use REACH to engage in systematic compromise and a pedagogical approach to chemical risks. Information and resource asymmetry make co-management necessary for the implementation of the regulation, but comes at the cost of the " no data, no market " principle.